DAMPAK PROGRAM KELUARGA HARAPAN (PKH) TERHADAP RUMAH TANGGA SANGAT MISKIN (RTSM) DALAM MENINGKATKAN PENDIDIKAN Di DESA TELUK PAUH KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Miftahul Rizki; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this research is to find out the implementation of PKH activities are on target and To find out how the results of PKH activities to families who receive. The location of this research was conducted in The Village of Teluk Pauh Keamatan Pangean with the number of respondents 35 people. Data analysis method using survey research method and using descriptive quantitative method. The results showed that the Family Of Hope Program has been running well this is known from the results of respondents' answers of 34 people or 97.1% answered well. Aspects of Education that the government has been able to improve the education of very poor households through the Family of Hope Program (PKH) has helped poor households in sending children to school. With PKH Education for poor families/households is guaranteed. It's just that PKH in Teluk Pauh Village, Pangean District, Kuantan Singingi Regency, distribution of PKH assistance has not been on target as seen from the recipients of PKH assistance already there who are prosperous and can meet their daily needs. This is because the data used for the determination of beneficiaries is determined by data at the national level by using data in the previous year / data used is invalid, while when there is a status switch on rtsm in the region must go through a long process in order to be replaced or removed from the list of beneficiaries. Keywords: PKH, RTSM, Education